Xis and Fis proteins prevent site-specific DNA inversion in lysogens of phage HK022. - Dorgai, L (1993)
HK022, a temperate coliphage related to lambda, forms lysogens by inserting its DNA into the bacterial chromosome through site-specific recombination. The Escherichia coli Fis and phage Xis proteins promote excision of HK022 DNA from the bacterial chromosome. These two proteins also act during lysogenization to prevent a prophage rearrangement: lysogens formed in the absence of either Fis or Xis frequently carried a prophage that had suffered a site-specific internal DNA inversion. The inversion is a product of recombination between the phage attachment site and a secondary attachment site located within the HK022 left operon. In the absence of both Fis and Xis, the majority of lysogens carried a prophage with an inversion. Inversion occurs during lysogenization at about the same time as prophage insertion but is rare during lytic phage growth. Phages carrying the inverted segment are viable but have a defect in lysogenization, and we therefore suggest that prevention of this rearrangement is an important biological role of Xis and Fis for HK022. Although Fis and Xis are known to promote excision of lambda prophage, they had no detectable effect on lambda recombination at secondary attachment sites. HK022 cIts lysogens that were blocked in excisive recombination because of mutation in fis or xis typically produced high yields of phage after thermal induction, regardless of whether they carried an inverted prophage. The usual requirement for prophage excision was bypassed in these lysogens because they carried two or more prophages inserted in tandem at the bacterial attachment site; in such lysogens, viable phage particles can be formed by in situ packaging of unexcised chromosomes.